2022
DOI: 10.3390/molecules27217324
|View full text |Cite
|
Sign up to set email alerts
|

7-Hydroxycoumarin Induces Vasorelaxation in Animals with Essential Hypertension: Focus on Potassium Channels and Intracellular Ca2+ Mobilization

Abstract: Cardiovascular diseases (CVD) are the deadliest noncommunicable disease worldwide. Hypertension is the most prevalent risk factor for the development of CVD. Although there is a wide range of antihypertensive drugs, there still remains a lack of blood pressure control options for hypertensive patients. Additionally, natural products remain crucial to the design of new drugs. The natural product 7-hydroxycoumarin (7-HC) exhibits pharmacological properties linked to antihypertensive mechanisms of action. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Furthermore, a recent study showed that 7-hydroxycoumarin induces vasorelaxation in hypertensive rats and diminishes rat mesenteric arteries' responsiveness to α 1 -AR agonists challenge. 80 Thus, the potential of the coumarin scaffold for developing novel, selective α 1 -adrenoceptor ligands has precedent.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent study showed that 7-hydroxycoumarin induces vasorelaxation in hypertensive rats and diminishes rat mesenteric arteries' responsiveness to α 1 -AR agonists challenge. 80 Thus, the potential of the coumarin scaffold for developing novel, selective α 1 -adrenoceptor ligands has precedent.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Other groups have also described coumarin-piperazine derivatives as serotonin and dopamine receptor binding ligands, and to a lesser extent α 1 -AR ligands, , again focusing only on the α 1A -AR subtype. Furthermore, a recent study showed that 7-hydroxycoumarin induces vasorelaxation in hypertensive rats and diminishes rat mesenteric arteries' responsiveness to α 1 -AR agonists challenge . Thus, the potential of the coumarin scaffold for developing novel, selective α 1 -adrenoceptor ligands has precedent.…”
Section: Discussionmentioning
confidence: 99%